Phytochemical screening, antioxidant and antimicrobial activities of Citrus maxima (Burm.) Merr. - Barrion, A. S. A.; Dizon, E. I.; Hurtada, W. A.; Rodriguez, F. M. (2003)
Phytochemical constituents, antioxidant activity and antimicrobial activity of crude ethanolic extracts of pericarp and mesocarp fruit parts of Citrus maxima (Burm.) Merr., were investigated.
Phytochemical screening revealed the presence of phenols, tannins, saponins expressed in terms of mg catechin equivalents (CE) per 100ml and flavonoid expressed in terms of mg gallic acid equivalents (GAE) per 100ml in both of the investigated fruit parts. A stronger antioxidant activity and higher amounts of phenol, tannin, flavonoid and saponin were significantly noted in the pericarp as compared to the mesocarp extract. Presence of alkaloids was observed only in the pericarp sample extract however, terpenoids were found to be present in both sample extracts. The inhibition test showed that treating raw chicken neck with pericarp and mesocarp extracts using 100% concentration and 1:1 w/v ratio, significantly achieved a 1.63 and 1.77 log FU/g reduction in microbial activity, respectively, after 3 days of storage at 4°C. Although the results showed minimal inhibitory effect, these data provide evidence that the pericarp and mesocarp parts of the Citrus maxima (Burm.) Merr., can be potential source of natural antimicrobial and antioxidizing agents.
Keywords: Citrus; Phytochemicals